Interferon-γ and celecoxib inhibit lung-tumor growth through modulating M2/M1 macrophage ratio in the tumor microenvironment - Ren F; Fan M; Mei J; Wu Y; Liu C; Pu Q; You Z; Liu L (Dove Medical Press, 2014)
Fuqiang Ren,1,2,* Mingyu Fan,1,2,* Jiandong Mei,1,2 Yongqiang Wu,3 Chengwu Liu,1,2 Qiang Pu,1,2 Zongbing You,4–9 Lunxu Liu1,2 1Department of Thoracic Surgery, West China Hospital, 2Western China Collaborative Innovation Center for Early Diagnosis and Multidisciplinary Therapy of Lung Cancer, 3Regenerative Medicine Research Center, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 4Department of Structural and Cellular Biology, 5Department of Orthopaedic Surgery, 6Tulane Cancer Center, 7Louisiana Cancer Research Consortium, 8Tulane Center for Stem Cell Research and Regenerative Medicine, 9Tulane Center for Aging, Tulane University Health Sciences Center, New Orleans, LA, USA *These two authors contributed equally to this study Abstract: Tumor-associated macrophages play an important role in tumor growth and progression. These macrophages are heterogeneous with diverse functions, eg, M1 macrophages inhibit tumor growth, whereas M2 macrophages promote tumor growth. In this study, we found that IFNγ and/or celecoxib (cyclooxygenase-2 inhibitor) treatment consistently inhibited tumor growth in a mouse lung cancer model. IFNγ alone and celecoxib alone increased the percentage of M1 macrophages but decreased the percentage of M2 macrophages in the tumors, and thus the M2/M1 macrophage ratio was reduced to 1.1 and 1.7 by IFNγ alone and celecoxib alone, respectively, compared to the M2/M1 macrophage ratio of 4.4 in the control group. A combination of IFNγ and celecoxib treatment reduced the M2/M1 macrophage ratio to 0.8. Furthermore, IFNγ and/or celecoxib treatment decreased expression of matrix metalloproteinase (MMP)-2, MMP-9, and VEGF, as well as the density of microvessels in the tumors, compared to the control group. This study provides the proof of principle that IFNγ and/or celecoxib treatment may inhibit lung-tumor growth through modulating the M2/M1 macrophage ratio in the tumor microenvironment, suggesting that IFNγ and celecoxib have potential to be further optimized into a new anticancer therapy. Keywords: tumor-associated macrophages, M1 macrophages, M2 macrophages, lung cancer, interferon-γ, celecoxib